2020
DOI: 10.17784/mtprehabjournal.2018.16.476
|View full text |Cite
|
Sign up to set email alerts
|

Physical inactivity and associated factors in adults of a basic health unit: An observational cross-sectional study

Abstract: Background: Physical inactivity (PI) is one of the most important risk factors that contribute to the development of chronic diseases, including cardiovascular diseases. Objective: To analyze the prevalence and associated factors with PI in adults from a Basic Health Unit in the city of Uraí, state of Paraná. Methods: An observational, descriptive, cross-sectional study was performed at Basic Health Unit of Uraí, and 100 subjects of both genders were evaluated, the average age of 47.55 ± 17.13 years. The data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
0
1
Order By: Relevance
“…In this study of insufficiently active Turkish adults, BMI did not differ significantly between those who were completely inactive and those who were marginally active. These results contrast with those of prior studies which have reported negative associations between physical activity and BMI (ODPHP, ; Silva et al, ; Vancampfort, Stubbs, & Koyanagi, ). Notably, adults in the present study had a mean BMI of 24.7, whereas mean BMIs in the United States (US) are 29.1 for men and 29.6 for women (Fryar, Kruszon‐Moran, Gu, & Ogden, ).…”
Section: Discussioncontrasting
confidence: 99%
“…In this study of insufficiently active Turkish adults, BMI did not differ significantly between those who were completely inactive and those who were marginally active. These results contrast with those of prior studies which have reported negative associations between physical activity and BMI (ODPHP, ; Silva et al, ; Vancampfort, Stubbs, & Koyanagi, ). Notably, adults in the present study had a mean BMI of 24.7, whereas mean BMIs in the United States (US) are 29.1 for men and 29.6 for women (Fryar, Kruszon‐Moran, Gu, & Ogden, ).…”
Section: Discussioncontrasting
confidence: 99%